ASSESSEMENT OF WATER QUALITY OF DIYALA RIVER USING OVERALL INDEX OF POLLUTION (OIP) IN IRAQ - D.W.K.Alsaadoon,; F. M. Hassan,; W. M. Mahdi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The present study was performed to assess the seasonal changes in the water quality of Diyala River (Diyala Governorate, Iraq), from five sites along the river during the period from September 2020 to April 2021, by applying the Overall Index of Pollution (OIP). OIP is one of the reliable indicators in evaluating the quality of surface water. To calculate the value of the OIP, twelve parameters were measured in the water samples, which are (water temperature, pH, electrical conductivity, dissolved oxygen, biological oxygen demand, total hardness, calcium, magnesium, total dissolved solids, total alkalinity, and concentrations of dissolved nitrates and phosphates). The results showed spatial and temporal variation of physicochemical parameters. The obtained values of OIP ​​(1.72-2.72) revealed acceptable water quality in some sites to slight pollution in the others sites. The current study recommends establishing a novel program for the maintenance and control of Iraqi waters. Such program should be based on scientific means to handle changes that occurred during the past years, such as insufficient release of Iraq’s water shares by neighboring countries, low-rate precipitation rates, and practices of water abuse committed by the population.